2021
DOI: 10.5435/jaaos-d-21-00433
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Severe Acetabular Bone Loss Using a Tantalum Acetabular Shell and a Cemented Monoblock Dual Mobility Acetabular Cup

Abstract: As the number of revision total hip arthroplasty increases, innovative solutions to complex problems are needed to address challenges posed by these complex cases. Severe acetabular bone loss, including cases of pelvic discontinuity, is a notable challenge with few solutions. Hip instability after revision arthroplasty remains one of the leading causes of revision and patient morbidity. The use of pelvic distraction and a press-fit tantalum shell for chronic discontinuity and posterior column open reduction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Recently, DM cups intended for cementation have become available. In some circumstances, these cemented constructs are advantageous as they allow correction of effective acetabular position (both acetabular version and inclination) and for the use of DM when modular options are not available, facilitating the retention of well-fixed acetabular components during revision THA [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, DM cups intended for cementation have become available. In some circumstances, these cemented constructs are advantageous as they allow correction of effective acetabular position (both acetabular version and inclination) and for the use of DM when modular options are not available, facilitating the retention of well-fixed acetabular components during revision THA [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, cemented DM constructs—that is, a monoblock DM cup, designed for cementation, cemented into an existing acetabular component—offer a viable solution. This technique has been biomechanically validated [ 21 ], and several small studies [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ] have reported favorable outcomes at early follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the authors reported rates of all-cause acetabular survival from re-revision of 96.7% at 6 months, 93.3% at 1 year, and 89.7% at 2 years 9 . Physicians should be aware of the possibility for intra-prosthetic dislocations, as although this complication is rare, it has been reported in the literature 7,10 . Important Tips:…”
mentioning
confidence: 99%
“…A cemented dual-mobility implant can be utilized in a well-fixed acetabular shell without evidence of loosening or osteolysis. Rationale: Dual-mobility implants have become increasingly utilized because of their advantages: (1) ability to decrease dislocation rate without increasing constraint and (2) increasing range of motion with reduced impingement risk [2][3][4][5][6][7][8] . These implants are particularly useful in the setting of revision cases with large acetabular bone defects.…”
mentioning
confidence: 99%
See 1 more Smart Citation